Treatment decision-making process after an anterior cruciate ligament injury: patients’, orthopaedic surgeons’ and physiotherapists’ perspectives - Hanna Tigerstrand Grevnerts; Barbro Krevers; Joanna Kvist (BMC Musculoskeletal Disorders, 2022)
Abstract Objective To investigate the treatment decision-making process after an anterior cruciate ligament (ACL) injury from patients’, orthopaedic surgeons’ and physiotherapists’ perspectives. Methods The study is a part of the NACOX study, which is designed to describe the natural corollaries after ACL injury. For the present study, a subgroup 101 patients were included. Patients, their orthopaedic surgeons and their physiotherapists, answered a Shared Decision-Making Process (SDMP) questionnaire, when treatment decision for ACL reconstruction surgery (ACLR) or non-reconstruction (non-ACLR) was taken. The SDMP questionnaire covers four topics: “ informed patient”, “ to be heard”, “ involvement” and “ agreement”. Results Most (75–98%) patients considered their needs met in terms of being heard and agreement with the treatment decision. However, fewer in the non-ACLR group compared to the ACLR group reported satisfaction with information from the orthopaedic surgeon (67% and 79%), or for their own involvement in the treatment decision process (67% and 97%). Conclusion and practice implications Most patients and caregivers considered that patients’ needs to be informed, heard and involved, and to agree with the decision about the treatment process, were fulfilled to a high extent. However, patients where a non-ACLR decision was taken experienced being involved in the treatment decision to a lower extent. This implies that the non-ACLR treatment decision process needs further clarification, especially from the patient involvement perspective.